THE ROLE OF FINANCIAL STRUCTURE, BUSINESS DRIVE, BUSINESS ENVIRONMENT ON DECISION TO USE AN EXTERNAL AUDITOR ON SMES: EVIDENCE FROM ASEAN COUNTRIES - Jonathan Jonathan; Moch. Doddy Ariefianto; Rindang Widuri (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2021)
The research examined the role of financial structure, business drive, and business environment that resulted in external audit service adoption in small and medium-sized enterprises (SMEs) within ASEAN countries. Source of data were from the 2015 and 2016 World Bank Enterprise Survey. The research discovers that external audit service adoption is significantly influenced by financial structure, business motivation, and business environment. Additionally, we take into account a number of control variables, including sales, ownership structure, industry sector, and country of origin. The findings indicate a significant positive correlation between sales, ownership structure (partnership vs. sole proprietorship), and external audit adoption for SMEs. From a country-of-origin perspective, it is concluded that audit adoption is significantly higher in Malaysia and the Philippines than in Vietnam. However, audit adoption in Indonesia is significantly lower than in Vietnam, both in terms of awareness and implementation. Other points of interest can be seen in the interaction regression between countries, which indicates the degree of complexity associated with audit adoption when country of origin is taken into account. One significant policy implication is that SMEs can leverage external auditor services to support their growth and, in turn, the economy of the corresponding country.